Pengaruh Word of Mouth, Citra Perusahaan dan Kepercayaan Terhadap Keputusan Pembelian Produk PT. Penta Valent Medan - Fanny Amalia; Adelina Lubis; Sugito Sugito (Universitas Medan Area, 2022)
Decision making’s very important for individuals and organizations. The purchase decision is the final result of a thought and action in making a purchase decision to use, use, consume goods or services that meet their needs and desires. The purpose of this study was to determine the effect of word of mouth, corporate image and trust on product purchasing decisions of PT. Penta Valent Medan. This type of research is quantitative research. The population of this research is the consumers of PT. Penta Valent, totaling 202 dispensaries and hospitals in the city of Medan. The number of samples was 134 pharmacies and hospitals with the sampling technique using the Slovin formula. The data used are primary data and secondary data. Primary data is obtained from questionnaires and interviews, secondary data is obtained from literature, previous research and so on. The data analysis technique used multiple linear regression. The results of this study indicate that simultaneously the variables word of mouth, company image and trust have a positive and significant effect on product purchasing decisions of PT. Penta Valent Medan. Partial test shows that the variable word of mouth has a positive effect on purchasing decisions, the variable company image has a positive and significant effect on purchasing decisions and the variable trust has a positive effect on purchasing decisions.